Board conduct in banks - Agarwal, Samanvaya; Kamath, Saipriya; Subramanian, Krishnamurthy; Tantri, Prasanna (Journal of Banking & Finance, 2022)
We examine the minutes of Indian banks' board meetings and offer insights into the issues tabled and discussed in bank boards. We find that risk issues account for only 10% of the issues tabled with regulation and compliance accounting for the most (41%), followed by business strategy (31%). Majority of the issues are not deliberated in detail. We interpret the evidence as suggestive of under-investment in risk and over-investment in regulation and compliance by bank boards.